Informe de situación fitosanitaria - Región Centro Norte de Córdoba Informe - De Rossi, R.L; Guerra, F.A.; Lábaque, M.; Vuletic, E.; Plazas, M. C.; Guerra, G.D. (Informe de Situación Fitosanitaria, 2019)
Ninguno